DIVERSIFIKASI PRODUK OLAHAN GANYONG (Canna edulis Kerr.): SINERGI PETANI DAN UMKM KUE DALAM MEWUJUDKAN KETAHANAN PANGAN - Wiwit Probowati; Nova Santika Maharani; Adiba Kanza Az Zahra; Silvi Lailatul Mahfida; Manda Aminah Gailea; Nisa Aulia Andini; Arizona Firdonsyah; Ajeng Hidayat Basyarotus Zahra; Hanna Usyaroh Nur Hasanah (Jurnal Abdi Insani, 2026)
Ganyong (Canna edulis Kerr.) is an underutilized local tuber crop with potential as an alternative food source due to its high carbohydrate content and adaptability to diverse environmental conditions. However, its utilization remains limited, contributing to a gradual decline in its cultivation. Product diversification based on ganyong is an important strategy to increase the commodity’s added value while supporting local food diversification and food security. Strengthening collaboration between farmers as raw material producers and micro, small, and medium enterprises (MSMEs) as food processors is essential to expand the utilization of ganyong in food products. This activity was conducted through collaboration between the community service team of Universitas 'Aisyiyah Yogyakarta and the MSME partner “Sameera Cake and Snack” in Sleman. The program aimed to develop ganyong flour with a moisture content below 10% and evaluate its application as a substitute for wheat flour up to 50% in cookie production. The activities included technical assistance in harvesting and post-harvest handling, training in ganyong flour processing, product formulation and cookie production, and hedonic testing to assess consumer acceptance. The results showed that the partner successfully produced ganyong flour with a moisture content of <10%, while the MSME produced cookies with up to 50% substitution of ganyong flour. Hedonic testing involving 28 respondents indicated that the cookies were generally well accepted, with average scores of 3.3 for appearance and 3.1 for taste in the “like” category. These findings demonstrate that ganyong-based cookies have promising market potential. In addition, the program strengthened farmer–MSME collaboration and contributed to increasing the value of local food resources while supporting food diversification.